KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SMA NEGERI 1 KOTA TERNATE - Irfandi R. Hi Irfandi Mustafa (Manajer Pendididikan, 2022)
Abstract - The purpose of this study was to determine the principal's managerial leadership in the implementation of school-based management. Descriptive qualitative research method with data collection through observation, interviews and documentation. Data analysis of data reduction research, data presentation and conclusions. Checking the validity of the data using triangulation of methods and sources. The results showed that the principal's managerial was effective and efficient in planning, organizing, implementing and supervising the implementation of school-based management in SMA Negeri 1 Ternate City. Keyword: Managerial Leadership, Principal, School Based Management